A Research Design for Studying the Efficiency of Regional Policies In the North-West Region, Romania - Călin GHIOLȚAN (Transylvanian Review of Administrative Sciences, 2007)
The paper endeavors to build a possible research design format for studying the efficiency of regional policies in the North-Vest region, Romania. In the first two sections the paper sets forth a series of research objectives and highlights the epistemological framework used in building the research hypothesis. In the last sections the author discusses methodological issues such as the proposed research methods and instruments, validity and fidelity, and sampling.